1993
DOI: 10.1126/science.8105536
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DPB1 Glutamate 69: a Genetic Marker of Beryllium Disease

Abstract: Chronic beryllium disease (CBD) is a lung disorder related to beryllium exposure and is characterized by the accumulation in the lung of beryllium-specific CD4 + major histocompatibility complex (MHC) class II-restricted T lymphocytes. Evaluation of MHC class II genes in 33 CBD cases and 44 controls has shown a negative association with HLA-DPB1 * 0401 ( P < 0.001) and a positive association with HLA-DPB1 * 0201 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
311
0
7

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 448 publications
(334 citation statements)
references
References 32 publications
16
311
0
7
Order By: Relevance
“…Its role in antigen presentation has been established for viral and bacterial antigens and in alloreactivity (57). One of the strongest HLA class II genetic associations with immunological disorders is the presence of a glutamic acid at position HLA-DP ␤69, which confers susceptibility to metal-induced disorders as chronic beryllium disease and hard metal diseases (58,59). MIF association with other HLA class II polymorphic variants cannot be excluded at the present time and will be a matter of further investigations.…”
Section: Mif Peptidementioning
confidence: 99%
“…Its role in antigen presentation has been established for viral and bacterial antigens and in alloreactivity (57). One of the strongest HLA class II genetic associations with immunological disorders is the presence of a glutamic acid at position HLA-DP ␤69, which confers susceptibility to metal-induced disorders as chronic beryllium disease and hard metal diseases (58,59). MIF association with other HLA class II polymorphic variants cannot be excluded at the present time and will be a matter of further investigations.…”
Section: Mif Peptidementioning
confidence: 99%
“…An association has been shown between certain DPB1 alleles and susceptibility to particular diseases. [13][14][15][16][17][18] HLA-DP-specific T-cells have been isolated from skin biopsies at the onset of graft-versushost-disease (GvHD) in HLA-DP mismatched transplants. 19 It has also been reported that most leukaemic blasts are accessible to direct lysis by allogeneic HLA-DPspecific T cells, suggesting that these cells may also be responsible for an antileukaemic effect.…”
mentioning
confidence: 99%
“…HLA-DPB1*05:01 does not have glutamic acid at position 69, however, HLA-DPB1 *09:01 does. On the other hand, another study revealed a strong association between glutamic acid at position 69 in HLA-DPB1 and chronic beryllium disease (22). It has been suggested that HLA-DPB1 may play an important role in antigen presentation and recognition in chronic granulomatous diseases.…”
Section: Discussionmentioning
confidence: 99%